Identification of Polymorphism Growth Hormone Gene in Local Chickens Resulting from Three Breed Crosses - Harini Nurcahya; Sri Darwati; Isyana Khaerunnisa; Ida Wiryanti (Universitas Nasional Jakarta, 2021)
Local chicken has an important role as a source of animal protein producing eggs and meat. Local chicken has the advantage of being able to adapt to hot weather and be more resistant to disease. However, there are still weaknesses, namely relatively slow growth and relatively low egg production. Therefore, one way to overcome these weaknesses is by holding selection and crossing. Local chickens used for crossing in this study were sentul, kampung and kedu chicken. In connection with the growth of chickens that are slow and low in productivity of local chickens, it is necessary to examine the factors that influence growth and productivity. The hormones that have an effect on growth are GH (Growth Hormone), so that the characteristics of the gene of growth in local chickens from the cross can be known.The purpose of this study was to detect the characteristics of the Growth Hormone gene in local chickens resulting from Three Breed Crosses . The research material used in this study was forty local chickens produced by cross-sentul, kampung and kedu chicken. To find out GH gene polymorphism is by PCR-RFLP with cutting enzyme EcoRV.The results of the GH gene study in sentul, kampung and keducrossed chickens are polymorphic and are in the Hardy-Weinberg equilibrium state. Kampung chicken cross population was polymorphic for GH|EcoRV loci and the GG genotype was predominant in this population. G allele frequency in kampung,kedu and sentul chicken cross population is higher than the A allele. The highest genetic diversity was observed at kampung,kedu and sentul chicken cross and the heterozygosity value was lowcategory.